Some geotechnical soil properties of western bank of Khor Al-Zubair channel coast at Khor Al-Zubair Port location, southern Basrah, Iraq - Muttashar, W.R. (Mesopotamian Journal of Marine Sciences, 2022)
Five Offshore Boreholes have been drilled by the National Construction Center at Basrah with cooperation the Marine Science Center/Basrah University, together with three Onshore Boreholes at the western bank of Khor Al-Zubair channel during July 2009. The drilling machine of Auger type has been used for drilling. Representative soil samples were taken at appropriate intervals ranged between 0.5 and 2.0 meters depth or where the stratum has been changed. Onshore boring depths ranged from 19.0 – 20.5 m, from natural ground surface, while, the offshore borings were from 7-16 m from the bed level. The depths of drilling reached the bedrock which is hard enough to require N-value of more than 50 blows. Standard Penetration Test (SPT) has been carried out for each 2m depths. Grain size analysis, moisture content, Atterberg limits of these soils were also determined. The results show that there are two main strata making up the coast bank of the navigational channel of Khor Al-Zubair. First is Marly silty Clay or fat clay soil which has of a thickness18 m, and gradually changes from very soft- m.stiff to stiff-v.stiff which belongs to the Hammar deposits. The second is Silty Sand layer which has two types of sandy soil, these are: (1) borrowed Back filled layer as surficial compaction soil with of a thickness 2.0 m, and (2) are interacted lenses stratum between the gray stiff silty clay and the hard brown silty clay in the near and onshore Boreholes which belongs to the Dibdiba formation.